Effects of strain rate on the mechanical and fracturing behaviors of rock-like specimens containing two unparallel fissures under uniaxial compression. Issue 110 (July 2018) - Feng, Peng; Dai, Feng; Liu, Yi; Xu, Nuwen; Zhao, Tao
Abstract: Rocks containing unparallel fissures are likely to be subjected to dynamic loading resulting from earthquakes in various civil engineering structures. Since dynamic loading rate significantly affects the mechanical behaviors of fissured rocks, understanding the mechanical properties and fracture mechanism of fissured rocks under different loading rates is thus crucial in rock engineering applications. This study investigates the effects of strain rate on the mechanical and fracturing behaviors of rock-like specimens containing two unparallel fissures with varying inclination angles ( α 2 ). Our experimental results demonstrate that α 2 and strain rate significantly affect the strength and deformation characteristics and the failure modes of fissured specimens. Both the strength and elastic modulus of the rock-like specimens highly depend on the strain rates, and the strain rate dependence is more sensitive for fissured specimen than that for the intact specimen. Under the same strain rate, the strength of fissured specimens decreases as α 2 increases up to 60°, and then increases. The fissured specimens with greater α 2 are characterized by higher elastic modulus. Furthermore, the fracture mechanism of the fissured specimen is numerically revealed, and the energy characteristics of fissured models are also analyzed on a micro-level. Highlights: Strength and deformation characteristics highly depend on the strain rate. The failure modes of fissured specimens exhibit high strain rate dependence. Energy characteristics of fissured models are analyzed on a micro-level. The fracture mechanism of fissured specimen under dynamic strain rate is numerically revealed.